2019
DOI: 10.1186/s13071-019-3632-3
|View full text |Cite
|
Sign up to set email alerts
|

ProHeart® 12, a moxidectin extended-release injectable formulation for prevention of heartworm (Dirofilaria immitis) disease in dogs in the USA for 12 months

Abstract: Background The efficacy of an extended-release injectable moxidectin (0.5 mg/kg) suspension (ProHeart® 12) (PH 12) in preventing the development of Dirofilaria immitis in dogs for 12 months was investigated in laboratory and field studies in the USA. Methods In each of two laboratory studies, 20 dogs ≥ 12 months of age were randomly allocated to receive a subcutaneous injection of saline or PH 12 on Day 0 and were then inoculated with 50 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(50 citation statements)
references
References 30 publications
4
40
0
Order By: Relevance
“…The presence of microfilaremia in this dog after receiving an ML for 11 consecutive months strongly supports that this dog was infected with a ML-resistant D. immitis strain [17,18]. Another recent clinical field study [19] which was also conducted in heartworm-endemic regions of the USA, including the LMRV, showed that moxidectin in an extended-release injectable formulation (ProHeart ® 12; Zoetis) provided 100% heartworm prevention in 236 dogs compared to the 98.8% efficacy provided in the 218 dogs treated monthly with Heartgard ® Plus. Of the four Heartgard ® Plus dogs that were positive for D. immitis antigen in that study, three were also positive for D. immitis microfilariae with confirmed monthly compliance; this also supports the likelihood that these dogs were infected with an ML-resistant strain of D. immitis.…”
Section: Discussionsupporting
confidence: 71%
“…The presence of microfilaremia in this dog after receiving an ML for 11 consecutive months strongly supports that this dog was infected with a ML-resistant D. immitis strain [17,18]. Another recent clinical field study [19] which was also conducted in heartworm-endemic regions of the USA, including the LMRV, showed that moxidectin in an extended-release injectable formulation (ProHeart ® 12; Zoetis) provided 100% heartworm prevention in 236 dogs compared to the 98.8% efficacy provided in the 218 dogs treated monthly with Heartgard ® Plus. Of the four Heartgard ® Plus dogs that were positive for D. immitis antigen in that study, three were also positive for D. immitis microfilariae with confirmed monthly compliance; this also supports the likelihood that these dogs were infected with an ML-resistant strain of D. immitis.…”
Section: Discussionsupporting
confidence: 71%
“…ProHeart ® 12 and ProHeart ® SR-12 are brand names of the same extended-release microsphere formulation of moxidectin, the former being marketed in the USA and the later in Australia, Japan, southeast Asia and Brazil. Recently published studies report the efficacy of a single administration of injectable moxidectin at 0.5 mg/kg (1 ml/20 kg) by subcutaneous (SC) injection as a heartworm preventative and safety of 1×, 3× and 5× the dose every six months for three treatments in normal beagles beginning at six months of age and as high as 5× the use rate in reproducing animals, ivermectin-sensitive dogs, and heartworm-positive dogs [16,22].…”
Section: Introductionmentioning
confidence: 99%
“…Moxidectin was selected for testing here primarily due to its higher intrinsic potency against filarial nematodes when plasma concentrations provide a longer parasite exposure to the drug compared with other ML, including against ML-resistant heartworm strains [ 16 18 ]. Pharmacokinetic characteristics of moxidectin, including its high distribution in lipid tissues, reduced metabolism, and long half-life, contribute to its accumulation and high potency [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Given the comparability between the PH 6 PV profile and that of PH 12 internationally, that owner non-compliance continues to be an issue with monthly-use heartworm preventative products, and that the once-yearly dose interval for PH12 provides inherently superior compliance, Zoetis elected to seek approval for marketing of PH 12 in the USA. The safety objectives for PH 12 studies outlined in this article and in McTier et al [1] were extended as feasible to elucidating the origin and incidence of hypersensitivity-related responses if any should be observed.…”
Section: Introductionmentioning
confidence: 99%
“…At the site of injection, the tissue response and the morphologic characteristics of degrading microspheres were carefully evaluated for the type and character of inflammation. Due to the anticipated low incidence of these reactions, the study of McTier et al [1] was doubled in size with hope that hypersensitivity-related reactions might be observed and more carefully described.…”
Section: Introductionmentioning
confidence: 99%